Potensi Senyawa Salisilanilida Dari Minyak Gandapura Sebagai Antiinflamasi dan Analgetik Secara In Vivo - Dhimas Adhityasmara; Eka Susanti Hanhadyanaputri; Erwin Indriyanti (Universitas Wahid Hasyim Semarang, 2024)
Administration of non-steroidal anti-inflammatory drugs (NSAIDs) is the first therapeutic choice for the treatment of pain and inflammation. Several existing amide derivatives show their properties as anti-inflammatory, antidegenerative, anticancer, antimicrobial and analgesic, one of which is salicylanilide. The precursor for salicylanilide synthesis is carboxylic acid, using natural methyl salicylate from gondopuro oil and amines sonochemically with the help of Decyclocarbodiimide (DCC) coupling reagent. The research aims to carry out the synthesis of amide derivatives using DCC coupling reagent with the sonochemical method in 7 hours. Identification of synthetic compounds by spectrum elucidation using infrared spectrophotometry (FTIR-ATR), GC-MS and in-vivo anti-inflammatory and analgesic activity tests. In this study, the mixture was sonicated for 7 hours at a temperature of ±0oC, then left in the refrigerator overnight, evaporated at a temperature of 65oC. The precipitate formed was filtered using Buchner, washed using cold distilled water and washed again using methanol. The crystals obtained were then dried in an oven at 40ºC until dry, then the % yield of the synthesized compound was determined. Tests include organoleptic tests, melting point, solubility, FTIR, GC-MS In vivo anti-inflammatory and analgesic activity tests. The research results showed that salicylanilide compounds could be synthesized in 7 hours with a % yield of 27.55%. The resulting synthesis can melt from a temperature of 218-222°C and can dissolve in methanol, ethanol, chloroform and ether but does not dissolve in distilled water. FTIR testing on salicylanilide compounds showed the presence of phenolic -OH, aromatic C-H, C=O amide and aromatic C=C groups. The synthesized compound produced an abundance of 2.43%. The highest percentage of anti-inflammatory power was at dose 3 synthesis (7.56 mg/ 200 grams of rat body weight) at 44.46% and the highest analgesic effect was at dose 4 synthesis (10.08 mg/ 200 grams Rat BW)